2021
DOI: 10.12659/msm.935075
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of 42 Patients with COVID-19 infection and a History of Hepatitis C Virus Infection and Thyroid Disease with Follow-Up Thyroid Function and Autoantibody Testing

Abstract: Background Thyroiditis is an important extrahepatic association in chronic hepatitis C virus (HCV) infection. There have been reports of an association between SARS-CoV-2 infection and the onset or re-activation of autoimmune hypothyroidism. Therefore, we performed this prospective observational study of 42 patients with COVID-19 infection and a history of hepatitis C virus infection and thyroid disease with follow-up thyroid function and autoantibody testing. Material/Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…While patients with autoimmune thyroiditis had a significant increase in anti-thyroid peroxidase antibodies (ATPO) and anti-thyroglobulin antibodies (anti-Tg) levels at a 1-month follow-up after contracting the respiratory infection, patients with euthyroidism had a significant decrease in thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4) levels. As such, it was concluded that thyroid involvement and its markers should not be overlooked [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…While patients with autoimmune thyroiditis had a significant increase in anti-thyroid peroxidase antibodies (ATPO) and anti-thyroglobulin antibodies (anti-Tg) levels at a 1-month follow-up after contracting the respiratory infection, patients with euthyroidism had a significant decrease in thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4) levels. As such, it was concluded that thyroid involvement and its markers should not be overlooked [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cristinel et al reported increased TPOAb and TgAb levels in patients with autoimmune thyroid disease (AITD) and a history of chronic hepatitis C 1 month after SARS-CoV-2 infection 18…”
Section: Discussionmentioning
confidence: 99%
“…In the thyroid, these receptors make it a suitable target for virus entry [ 1 , 6 8 ]. Alongside the ACE-2 receptor, the TMPRSS2 receptor also exists on the surface of the thyroid gland, which is a route for the virus entry into the cells [ 9 11 ]. The SARS-CoV-2 seems to directly affect the thyroid gland and also the thyroid gland concerning a systemic inflammatory reaction [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the ACE-2 receptor, the TMPRSS2 receptor also exists on the surface of the thyroid gland, which is a route for the virus entry into the cells [ 9 11 ]. The SARS-CoV-2 seems to directly affect the thyroid gland and also the thyroid gland concerning a systemic inflammatory reaction [ 7 , 9 ]. An autopsy sample taken from the thyroid gland after death showed that COVID-19 directly infected the thyroid gland and caused the dysfunction of these glands [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation